A Reply to Theodori, Luloff, Brennan, and Bridger. (11th February 2016) - Flaherty, Jeremy; Cope, Michael R.
Abstract: Theodori et al. (2016) take issue with our presentation of the interactional field theory of community, asserting that, according to interactional field theory, (1) community does not equate with community field; (2) community does not emerge out of the community‐oriented actions of individuals; as well as making various other charges. In our reply, we refute their points, and demonstrate how Theodori et al., themselves, often provide the best evidence against their own arguments.